( Studi Kasus Analisis Rendahnya Partisipasi Masyarakat Pada Implementasi Program Nasional Pemberdayaan Masyarakat Mandiri Di Desa Ketangirejo Kecamatan Godong Kabupaten Grobogan ) - Imam Luqmana; Yuwanto .; Wiwik Widayati (Journal of Politic and Government Studies, 2014)
Indonesia's handling of poverty already made efforts to complete this one with the program PNPM Mandiri is a program that provides assistance to communities in the form of physical or nonphysical development funding which is stimulant with community empowerment. The participation of the community in the village of Ketangirejo District of Grobogan Godong planning, program implementation PNPM Mandiri is still low. Low level of community participation in program PNPM Mandiri can be caused by several factors, including the socialization process of the Government's apparatus is not going well, the level of understanding and acceptance of the information society is still low.Describing the results of research and used to approach descriptive quantitative. The method of collecting data is through interview and a questionnaire that is done with the election of respondents had to use the framework of the sample or of sampling the frame and pemilihan respondents conducted by the technique of adoption of a random sample simpleIn General, this results in a low level of community participation to the PNPM Mandiri program is more affected by the lack of novasi of the officer executing PNPM Mandiri in carrying out socialization in society. From the process of socialization of society less participate because in the socialization of PNPM Mandiri just invited people only, so the effect on the low level of public knowledge of program proposals.Hence, requires support and cooperation in a socialization of all the elements of the government ( a public figure ) and society together support the process of pnpm program in the village of ketangirejo. As a well, the condition of a social economy and education necessary to have a program of economic improvement from the government to improve the conditions.Keywords: street vendors, Cooperation, Government and Private